Food Security and Climate Change: Differences in Impacts and Adaptation Strategies for Rural Communities in the Global South and North - Raj, Subhashni; Roodbar, Sam; Brinkley, Catherine; Wolfe, David Walter (Frontiers in Sustainable Food Systems, 2022)
This research highlights the mismatch between food security and climate adaptation literature and practice in the Global North and South by focusing on nested case studies in rural India and the United States during the COVID-19 pandemic. The United States is one of the wealthiest countries in the world, but also has one of the largest wealth gaps. Comparatively, India has one of the largest populations of food insecure people. To demonstrate how adaptive food security approaches to climate change will differ, we first review the unique climate, agricultural, demographic, and socio-economic features; and then compare challenges and solutions to food security posed by the COVID-19 pandemic. While both countries rely on rural, low-income farmworkers to produce food, the COVID-19 pandemic has highlighted how agricultural and food security policies differ in their influence on both food insecurity and global hunger alike. Emphasis on agricultural production in developing regions where a majority of individuals living in rural areas are smallholder subsistence farmers will benefit the majority of the population in terms of both poverty alleviation and food production. In the Global North, an emphasis on food access and availability is necessary because rural food insecure populations are often disconnected from food production.